2018
DOI: 10.1200/jco.2018.78.6426
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Monotherapy in Symptomatic, Treatment-Naïve Patients With Waldenström Macroglobulinemia

Abstract: Purpose Ibrutinib is active in previously treated Waldenström macroglobulinemia (WM). MYD88 mutations ( MYD88) and CXCR4 mutations ( CXCR4) affect ibrutinib response. We report on a prospective study of ibrutinib monotherapy in symptomatic, untreated patients with WM, and the effect of CXCR4 status on outcome. Patients and Methods Symptomatic, treatment-naïve patients with WM were eligible. Ibrutinib (420 mg) was administered daily until progression or unacceptable toxicity. All tumors were genotyped for MYD88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 35 publications
10
114
3
1
Order By: Relevance
“…10,11 Prospective studies have also reported that CXCR4 mutations are associated with lower response rates, delayed response attainment, and shorter PFS on ibrutinib. [12][13][14][15] However, these studies included heterogenous groups of CXCR4-mutated patients, and were not large enough to discriminate the effect of individual somatic variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Prospective studies have also reported that CXCR4 mutations are associated with lower response rates, delayed response attainment, and shorter PFS on ibrutinib. [12][13][14][15] However, these studies included heterogenous groups of CXCR4-mutated patients, and were not large enough to discriminate the effect of individual somatic variants.…”
Section: Resultsmentioning
confidence: 99%
“…5,10,11 CXCR4 mutations also confer both in vitro and clinical resistance to ibrutinib, particularly nonsense variants such as CXCR4 S338X . [10][11][12][13][14][15][16] In WM patients, CXCR4 S338X constitutes the most common CXCR4 mutation identified. 3,5 CXCR4 S338X is primarily subclonal to mutated MYD88, but shows a highly variable clonal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Responses to ibrutinib and survival are not only impacted by MYD88 L265P but also by CXCR4 mutations [100]. A few drugs targeting CXCR4 are currently under investigation, as the response rates with ibrutinib alone are lower in the patient population with mutated CXCR4 compared to those who have the CXCR4 signature [127,128]. The CXCR4 antagonist ulocuplumab (BMS-936564/MDX1338) is a fully human IgG monoclonal antibody that is being evaluated in combination with ibrutinib in a phase 1/2 clinical trial for patients with relapsed or refractory WM (RRWM) only, who harbor a CXCR4 mutation (NCT03225716).…”
Section: Waldenstrom's Macroglobulinemiamentioning
confidence: 99%
“…In previously untreated patients, ibrutinib monotherapy resulted in high response rates (no complete responses); these occurred slower in those carrying CXCR4 WHIM , but the follow-up is still short. 65 Ibrutinib is active in both rituximab-sensitive and rituximab-refractory patients. 62,63 In the initial phase 2 study, 5-year PFS was 60% and 5-year overall survival (OS) was 87%, but responses and PFS were better in patients with the MYD88 L265P /CXCR4 WT than the MYD88 L265P / CXCR4 WHIM genotype; among the few patients with MYD88 WT , the responses were minor and PFS short.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%